Optimizing aquaculture-scale common carp artificial reproduction: a novel approach to sperm cryopreservation using large-volume containers and elevated thawing temperatures - Sotnikov, Anatolii; Rodina, Marek; Gela, David; Boryshpolets, Sergii; Kholodnyy, Vitaliy; Kašpar, Vojtěch; Linhart, Otomar; Dzyuba, Borys (Frontiers in Marine Science, 2024)
The successful cryopreservation of common carp sperm is crucial for its application in aquaculture and selective breeding programs. This study investigates the efficacy of cryopreserving sperm in large containers (5 mL) with a low dilution rate (1:1) with cryoprotective mediumin three different cryoprotective mediums and thawing in different conditions. The developed method utilizes a low ionic (hypotonic) cryoprotective medium, a freezing with a controlled cooling rate, and hightemperature sperm thawing (60 °C). The investigation employs detailed spermatozoon motility assessment, revealing consistent post-thaw motility (32.3±14%) and initial curvilinear velocity (89±20 µm s -1 ) across 30 males. Principal component analysis was employed to reveal distinct populations of sperm cells exhibiting varying responses to cryopreservation. With the developed method, successful fertilization comparable to the non-frozen control group was achievedThe developed method achieved successful fertilization comparable to the non-frozen control group by using sperm from a single cryotube (2.5 mL, approximately 50*10 9 spermatozoa) to fertilize 200 g of eggs (1:120000 egg:spz). This novel approach demonstrates an effective cryopreservation protocol for common carp sperm in large-volume cryo containers in combination with low ionic cryomedia and high thawing temperature, providing methods well-suited for fisheries practices and selective breeding programs.